The Studentsâ Perception And Achievement Of English Reading Comprehension Using Cognitive Language Learning Strategy - Arifin, Riyadh Ahsanul; Faridi, Abdurrahman (English Education Journal, 2017)
This study aimedto analyze: (1) the application of âCLLSâ in learning English reading comprehension among the students of year 8 ofthe MTs. Maâarif Malangbong, (2) their perception toward the application of âCLLSâ, (3) their achievement on reading comprehension using âCLLSâ, (4) their problems in using âCLLSâ, and (5) the solutions to improve their knowledge and skill of using âCLLSâ. The analysis reveals that: (1) the application of âCLLSâ in learning English reading comprehension among the students of year 8 of the MTs. Maâarif Malangbong has run well, (2) the perception of students of year 8 of the MTs. Maâarif Malangbong toward the application of âCLLSâ was generally positive, only some students who show negative perception, (3) studentsâ achievement  on reading comprehension using âCLLSâ has generally increased moderately from 69,78 in 2013 to  72,20 in 2014 and to 74,60 that is in 2015, but this research also found that there were three students who had high achievement with negative perception on the application of the âCLLSâ, (4) studentsâ problems in using âCLLSâ involve: unstable emotion, lack of interaction, poor students understanding, bad perception, the surroundings, lack of vocabulary mastery, lack of grammar knowledge, and lack of media used by teachers, and (5) the solutions to improve studentsâ knowledge and skill of using âCLLSâ are: encouraging students to talk to teachers, and friends, (b) suggest students to have more often working in group outside of the schoolhours, (c) give enough explanation of the importance of English lessons, (d) explain that English is not a hard and difficult, (e) motivate students to continuously make serious effort in practicing English by creating better surroundings,(f) guide them to diligently read, (g) provide basic patterns that will be used, and (h) explain something through the media they have.